1996
DOI: 10.1016/s0896-6273(00)80178-6
|View full text |Cite
|
Sign up to set email alerts
|

LTP of AMPA and NMDA Receptor–Mediated Signals: Evidence for Presynaptic Expression and Extrasynaptic Glutamate Spill-Over

Abstract: We have addressed the expression of long-term potentiation (LTP) in hippocampal CA1 by comparing AMPA and NMDA receptor-(AMPAR- and NMDAR-) mediated postsynaptic signals. We find that potentiation of NMDAR-mediated signals accompanies LTP of AMPAR-mediated signals, and is associated with a change in variability implying an increase in quantal content. Further, tetanic LTP of NMDAR-mediated signals can be elicited when LTP of AMPAR-mediated signals is prevented. We propose that LTP is mainly expressed presynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
181
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(192 citation statements)
references
References 53 publications
9
181
0
1
Order By: Relevance
“…(C and D) When change in PPF is calculated using points ''b'' and ''c,'' there is a significant correlation between change in PPF and LTP (C, r ϭ 0.87, n ϭ 10, P Ͻ 0.005, linear regression shown) that is similar to that of the control data (D, E, data from C superimposed). different paradigm, an increase in p with LTP was also recently demonstrated by examining MK-801 occlusion of NMDA receptors in naive slices vs. after LTP induction (49).…”
Section: Discussionmentioning
confidence: 66%
“…(C and D) When change in PPF is calculated using points ''b'' and ''c,'' there is a significant correlation between change in PPF and LTP (C, r ϭ 0.87, n ϭ 10, P Ͻ 0.005, linear regression shown) that is similar to that of the control data (D, E, data from C superimposed). different paradigm, an increase in p with LTP was also recently demonstrated by examining MK-801 occlusion of NMDA receptors in naive slices vs. after LTP induction (49).…”
Section: Discussionmentioning
confidence: 66%
“…The enhanced neurotransmitter release at vertical intracortical connections after global sensory deprivation appears to be unique to adult sensory cortices, because global reductions in sensory activity in the developing somatosensory or visual cortices fail to modify neurotransmitter release (Finnerty and Connors, 2000;Philpot et al, 2001a). The deprivation-induced increase in release probability in the adult cortex enhances the likelihood that perisynaptic/extrasynaptic NMDARs may be activated by glutamate spillover (Kullmann et al, 1996), and future studies will be needed to investigate whether this spillover could be augmented by a decrease in glutamate reuptake (Shen and Linden, 2005). Nonetheless, our data are consistent with the idea that visual deprivation increases a perisynaptic/extrasynaptic population of ifenprodil-sensitive NMDARs that can be activated by glutamate spillover during bursts of high-frequency stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could represent a difference of expression in the transporter subtypes. GAT-3 expression has been reported to be low in the adult and may be developmentally regulated (Liu et al 1993;Minelli et al 1996), whereas GAT-1 expression is reported to be higher in the adult than the neonate (Yan et al 1997). Recordings in this study were made on animals primarily over the age of 15 days old, but Ͻ26 (19.39 Ϯ 0.46; n ϭ 146).…”
Section: Transporter Expressionmentioning
confidence: 99%